Data Management in IOT Applications - Sanakkayala SatyaNarayana, Dr; V. Sai Bharath, G; Sri Lakshmi Sahithi, Katakam; Sai Rutwik, Adusumilli (International Journal of Engineering and Technology, 2018)
With the technology leaping towards a new phase the next big that is happening is IOT and managing the huge amount of data that is being produced. To apprehend the real Internet of Things in which the entirely is interconnected, direct interactions between sensors and actuators, also known as bindings, are essential. As more and more devices are getting connected to the internet there is a lot of data that is being generated. We need to maintain the quality of data and it should be manageable for future use. Consequently, in evaluation to subsisting studies on smart cities we give a information driven edge depicting the central information administration methodologies employed to check consistency, interoperability, granularity and re-convenience of the information created by strategies for the fundamental Internet of Things( IoT) for smart cities. We try to find the proper communication between the devices and finally try to implement the details for a system. In this paper we are trying to do survey on how the large amount of data is being stored and various strategies for handling the data by using some architectures for the smart traffic system. We are trying to use the SWIFT architecture for analyzing the traffic in smart cities.Â Â